Informatics and Artificial Intelligence (AI) Education in Korea: Situation Analysis Using the Darmstadt Model - Dagyeom Lee; Ji-Yeon Hwang; Youngjun Lee; Seong-Won Kim (JOIV : International Journal on Informatics Visualization, 2022)
The Korean government has implemented various policies to support software (SW) and artificial intelligence (AI) education to secure national competitiveness since 2015. As the social impact of AI technology increased, AI became an integral component of the computer education curricula. SW and AI education projects have been promoted jointly to develop technical and human infrastructure supporting the â€œinformaticsâ€â€”the subject name of computer science (CS) education in Korea. However, a survey conducted by the Korean government showed that only a few respondents had AI education provided by public institutions such as schools. Therefore, this paper analyzes why AI education has not been well implemented and proposes discussions for improvement. The Darmstadt model, a systematic framework for analyzing CS education in the country, was chosen to analyze the documents. Between 2015 and 2021, 72 documents related to the computer education system, sociocultural factors, curricula, policies, teaching environment, tests, extra curriculum activities, and media were collected and qualitatively analyzed. The results were presented regarding the educational system, sociocultural factors, curriculum, policies, teachers, tests, extracurricular activities, and media. The results reveal that systematic and coherent curricula are required at all school levels, and it is also necessary to secure more education time to implement the curriculum. The number of informatics-computer teachers should be increased, and research to verify the teaching capacity of teachers is demanded. Finally, it is vital to build and manage a technical infrastructure.